Comparison of devices for monitoring of the ionosphere at the observatory Pruhonice - Beran Ladislav; Chmelař Pavel; Rejfek Luboš; Chum Jaroslav; Mošna Zbyšek (IEEE (Institute of Electrical and Electronics Engineers), 2015)
This electronic document is about comparison of the methods and systems for the measurement of the ionosphere used at the geophysical observatory Pruhonice (50N, 14.5E). Three systems for ionospheric monitoring are installed at the station. The first system for the monitoring of the ionosphere is Digisonde, the second system is dual frequency GNSS receiver and the third system is continuous Doppler sounding. Each system has its benefits and weaknesses which are compared in this paper
Porovnání zařízení pro měření ionosféry na observatoři Průhonice
Keywords: Continuous Doppler sounding; Digisonde; GNSS receiver; ionosphere; Total Electron Content (TEC); Spojitý Dopplerovský přijímací systém, Digisonda, GNSS přijímač, Ionosféra, Celková elektronová koncentrace (TEC)